Qualitative and Quantitative Analysis of Antipsychotic Drugs-A Spectroscopic Study - Bright, A.; Renuga Devi, T.S.; Gunasekaran, S. (Asian Journal of Chemistry, 2010)
Sertraline hydrochloride and olanzapine are basic compounds of pharmaceutical application for antidepressant and antipsychotic treatment, respectively. Sertraline comes under the category of aryl and aryloxyalkyl-amines antidepressant drugs. Olanzapine is a relatively new benzodiazepine which has been found useful in the treatment of schizophrenia. In the present work the FTIR and Raman spectra of these two drugs were recorded in the solid state. The fundamental modes of vibration were assigned based on the position, shape and relative intensity of the recorded spectra and in correlation with the vibrational bands of structurally related molecules. By employing FTIR spectral technique the quality of the drugs under various storage conditions have been studied. The assay of the tablets of these drugs were done using UV-visible spectroscopy and compared with the labeled amount.